Dampak RFID pada Stok Barang Retailer - Karmawan, I Gusti Made (ComTech: Computer, Mathematics and Engineering Applications, 2012)
The development of RFID technology (Radio Frequency Identification) offers some advantages, especially in goods distribution, supply chain and logistics. This technology works by putting a chip on an item as a replacement for barcodes that are widely used today. With the RFID technology, the process of goodsidentification becomes very easy and fast. Therefore, some large companies have started implementing and trust the system, especially the supermarket retailers although there are still some problems encountered in the application of this system, related to issues of privacy and data integrity problems. This paper discusses how RFID works and the impacts to the company related to profits and problems encountered during the application of this system.